Assessing Nitrogen Limitation in Inoculated Soybean in Southern Brazil - Vítor Gabriel Ambrosini; Sandra Mara Vieira Fontoura; Renato Paulo de Moraes; Walter Carciochi; Ignacio A. Ciampitti; Cimélio Bayer (Agrosystems, Geosciences & Environment, 2019)
Core Ideas Soybean yield did not respond to low starter fertilizer N rates in soils with high organic matter content. Nitrogen limitation tended to be greater in low compared with medium‐high yield levels. Nitrogen limitation is potentially related to lower contribution of N coming from biological nitrogen fixation (BNF) and mineralization. Overcoming potential N limitation in soybean [Glycine max (L.) Merr.] is a critical factor for sustaining plant nutrient demand and improving productivity. Following this rationale, a set of studies were executed in southern Brazil with the goals of quantifying yield response to early season fertilizer N rates (up to 40 kg ha−1), “starter N fertilization,” and to understand if soybean seed yields are limited by N (testing a non‐limiting N scenario) when grown in soils with medium to high organic matter content. The main key outcomes of this research were: (i) starter N fertilization did not increase yields compared with non‐fertilized soybean, potentially highlighting the absence of an early season N limitation; and (ii) N limitation was observed when soybean yields were compared with non‐limiting N scenario and it tended to be greater in low compared with medium‐high yield levels, potentially connected with co‐limitations on both N sources (N2 fixation and mineralization) to satisfy soybean N demand. Producing soybean in a sustainable manner implies focus on production practices to conserve and, potentially, to increase soil organic matter on a long‐term basis. Furthermore, it requires enhancing the biological N2 fixation process for satisfying the large plant N demand for achieving high soybean yields. Future research should be focused on understanding factors governing biological N2 fixation and N mineralization processes in soybean grown in soils with medium‐high organic matter content.